Analisis Kinerja Publikasi Dosen di Fakultas Ekonomi dan Bisnis dengan VOS Viewer - Tini Adiatma (Musamus Journal of Business & Management, 2024)
Lecturer publication performance is an important aspect in achieving higher education KPI and is related to one aspect of external quality assurance through accreditation activities. Publication is one of the lecturers' performances related to tridharma activities, namely research and community service. The aim of this research is to explore themes and relationships between authors in scientific publications carried out by lecturers at the Faculty of Economics and Business, Musamus University. This research was carried out using a bibliometric analysis approach, on lecturer publication data from 2018 to 2022. The research results showed that there were 314 articles published in that year. This research theme consists of 9 clusters, with 40 keywords. The most frequently used keywords are development, Papua, company, performance, case study, decision, motivation, difference and community. This theme is related to the research and service roadmap developed by the Faculty, namely entrepreneurship, government performance, company performance and regional development. Meanwhile, the relationship between authors, namely lecturers, can be clustered into 7 clusters. It is hoped that this research can provide an overview of institutions in developing more specific research themes based on the competencies possessed by lecturers.